THE MAIN PROBLEMS OF THE DEVELOPMENT OF SERVICE ACTIVITIES IN THE HOTELIER AND WAYS TO ELIMINATE THEM - Khamitov Mubin Khabibzhonovich (PT. Antis International Publisher, 2024)
General Background: The rapid advancement of digital technology has reshaped the global hotel industry, enhancing service quality and operational efficiency to meet evolving customer expectations. Specific Background: In Uzbekistan, efforts to align the hotel sector with global standards have intensified under the